Efficacy of progressive versus severe energy restriction on body composition and strength in concurrent trained women - Vargas-Molina, Salvador; Bonilla, Diego A.; Petro, Jorge Luis; Carbone, Leandro; García-Sillero, Manuel; Jurado‑Castro, José Manuel; Schoenfeld, Brad Jon; Benítez-Porres, Javier (Springer, 2023)
Purpose This study evaluated the concurrent training (CT) effect in combination with either progressive energy restriction (PER) or severe energy restriction (SER) on body composition and strength-related variables in resistance-trained women. Methods Fourteen women (29.5 ± 3.8 years; 23.8 ± 2.8 kg·m −2 ) were randomly assigned to a PER (n = 7) or SER (n = 7) group. Participants performed an 8-week CT program. Pre- and post-intervention measures of fat mass (FM) and fat-free mass (FFM) were assessed by dual-energy X-ray absorptiometry and strength-related variables were assessed through 1-repetition maximum (in the squat and bench press) and countermovement jump. Results Significant reductions in FM were observed in PER and SER (Δ = − 1.7 ± 0.4 kg; P = < 0.001; ES = − 0.39 and Δ = − 1.2 ± 0.6 kg; P = 0.002; ES = − 0.20, respectively). After correcting FFM for fat-free adipose tissue (FFAT), no signifi- cant differences for this variable were found either in PER (Δ = − 0.3 ± 0.1; P = 0.071; ES = − 0.06) or in SER (Δ = − 0.2 ± 0.1; P = 0.578; ES = − 0.04). There were no significant changes in the strength-related variables. No between-group differences were found in any of the variables. Conclusion A PER has similar effects to a SER on body composition and strength in resistance-trained women performing a CT program. Given that PER is more flexible and thus may enhance dietary adherence, it might be a better alternative for FM reduction compared to SER.
Keywords: Obesidad - Tratamiento; Ejercicio físico; Concurrent training; Calorie restricted diet; Fat reduction; Hypertrophy; Muscle strength; Resistance training